Corporate income tax in the EU, the Common Consolidated Corporate Tax Base (CCCTB) and beyond: is it the right way to go? - Valenduc, Christian (Brussels, 2018)
"This working paper reviews key elements of the debate around the Commission’s proposals to tackle the problem of low effective tax rates for multi-national companies by instituting a Common Corporate Tax Base (CCTB). The paper begins with a non-technical discussion of the main issues, including earlier OECD and G20 proposals, and their implications for European tax policy. It then discusses the relevance of the CCTB proposal and considers to what extent it could provide a comprehensive solution for the main issues at stake."